Prevalence of peripheral artery disease in the elderly population in urban and rural areas of Central Africa: the EPIDEMCA study. (29th August 2020) - Desormais, Ileana; Aboyans, Victor; Guerchet, Maëlenn; Ndamba-Bandzouzi, Bébène; Mbelesso, Pascal; Dantoine, Thierry; Mohty, Dania; Marin, Benoît; Preux, Pierre Marie; Lacroix, Philippe
Abstract: Objective: Data on peripheral artery disease in Africa are sparse and limited to urban areas. Given the urban/rural socio-economical gradient in these countries, we sought to determine the prevalence and risk factors of peripheral artery disease in urban and rural areas of two countries in Central Africa. Methods: Individuals ≥65 years old living in two urban and rural areas of the Republic of Central Africa (ROC) and the Central African Republic (CAR) were invited. Demographic, clinical and biological data were collected. Ankle-brachial index ≤0.90 defined peripheral artery disease. Results: Among the 1871 participants (age 73 years, 62% female) the prevalence of peripheral artery disease was 14.8%, higher in ROC than in CAR (17.4% vs . 12.2%, p = 0.007) and higher in females than males (16.6% vs . 11.9%, p = 0.012). The prevalence of peripheral artery disease increased with age, respectively at 10.9%, 14.9%, 15.1% and 22.2% for age bands of 65–69, 70–74, 75–79 and 80+years ( p < 0.001). Higher rates of peripheral artery disease were found in urban areas in ROC (20.7% vs . 14.4% in rural areas, p = 0.011), but not in CAR (11.5% vs . 12.9%, p = NS). In multivariate analysis, peripheral artery disease was significantly associated with age (odds ratio (OR): 1.03; p = 0.004), dyslipidaemia (OR: 1.88; p = 0.003), smoking (OR: 1.78; p = 0.003), obesity (OR: 1.98; p = 0.034) and underweight (OR: 1.49; p = 0.023). Regular alcohol drinking was associated with decreased risk of peripheral artery disease (OR: 0.73; p = 0.044). Conclusion: The prevalence of peripheral artery disease in the elderly is high in Africa, especially in females. In ROC, with a higher urban-rural socio-economic gradient, peripheral artery disease is more frequent in the urban areas.